Extended Village Head Tenure and Community Welfare in Tanggulangin - Agustino, Anggo Dwi; Mediawati, Fatimah (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Villages play a strategic role in Indonesia’s governance structure, particularly in delivering development and public services at the grassroots level. Specific Background: Regulatory changes extending village head tenure from six to eight years aim to provide leadership continuity, as implemented in Tanggulangin Village, Sidoarjo. Knowledge Gap: Empirical discussions on how extended tenure translates into tangible community welfare outcomes, especially under crisis conditions, remain limited. Aims: This study examines how extended village head tenure relates to community welfare in Tanggulangin. Results: Interview-based findings indicate that longer tenure allows completion of delayed programs, sustained infrastructure development, improved public services, and consistent economic empowerment initiatives, despite challenges such as leadership stagnation and technological adaptation. Novelty: The study highlights extended tenure as a governance mechanism enabling recovery and program continuity during and after the COVID-19 pandemic. Implications: The findings inform policymakers on balancing leadership continuity with accountability to support sustainable village development and community welfare.